Impact of right ventricular volume and function assessed by cardiac magnetic resonance imaging on outcomes in patients undergoing MitraClip implantation. (25th November 2020) - Spieker, M; Marpert, J; Afzal, S; Karathanos, A; Scheiber, D; Horn, P; Boenner, F; Kelm, M; Westenfeld, R
Abstract: Background: Right ventricular (RV) dysfunction is a predictor of poor clinical outcome in patients with heart failure and valvular heart disease. However, in patients undergoing MitraClip implantation, only limited data exist regarding the prognostic role of RV function and dimensions on outcomes. Previous studies suggested that RV dysfunction may be associated with poor clinical outcome following MitraClip, while other studies demonstrated contractionary results. Purpose: The purpose of this study was to assess whether cardiac magnetic resonance (CMR) imaging derived RV assessment can facilitate risk stratification among patients undergoing transcatheter mitral valve repair with the MitraClip. Methods: Sixty-one patients (mean age 77±9 years; 72% functional MR; logistic EuroScore 24±15) with severe mitral regurgitation (MR) were included and underwent CMR imaging and right heart catheterization prior MitraClip procedure. We divided patients into groups according to the presence of RV systolic dysfunction defined by RV ejection fraction (RVEF) <45%. Similarly, patients were separated into groups according to the presence of RV dilatation. For the assessment of RV dilatation, the RV end-diastolic volume index (RVEDVi) assessed by CMR was matched to age and gender specific reference values for each patient. All-cause mortality was assessed during one-year follow-up. Results: Patients with RV systolic dysfunction displayed increased left and right ventricular volumes as well as reduced LVEF (all p<0.05). Patients with RV dilatation showed increased left atrial area index (p=0.012) and had more advanced tricuspid regurgitation (p=0.028). Moreover, we observed a negative correlation between RVEDVi and PAPi (r=−0.231, p=0.087) and a positive correlation between RVEDVi and the ratio of right atrial (RA) pressure/ pulmonary artery wedge pressure (PAWP) (r=0.278, p=0.043). We found an inverse correlation between RVEF and systolic pulmonary artery pressure (r=−0.329, p=0.012) (Figure 3). During 12±1 month follow-up, 15 patients (25%) died. Kaplan-Meier survival analysis for 1-year mortality shows that patients with RV systolic dysfunction (p=0.026) and RV dilatation (p=0.005) had an increased 1-year all-cause mortality. Patients presenting with both, RV systolic dysfunction and RV dilatation, exhibited a very high 1-year mortality of 71% (p<0.001). Conclusion: The assessment of RV volumes and function by CMR imaging yields important prognostic information that enable an estimation of heart failure severity and prognosis. In this regard, not only RV systolic dysfunction, but also RV dilatation was associated with increased 1-year mortality, while patients presenting with both exhibit additive high mortality risk. Therefore, current criteria for patient selection that are mainly based on mitral valve characteristics only, should also consider RV volumes and function as can be accurately assessed by CMR. Funding Acknowledgement: Type of funding source: None